'Come and see the system in place' : Mediation Capabilities in Papua New Guinea’s Urban Settlements - Craig, David; Porter, Doug; Hukula, Fiona (World Bank, Washington, DC, 2017)
Although Papua New Guinea’s (PNG) urban settlements and mixed neighborhoods have a reputation for endemic violence, many local observers report some improvements in urban safety and security over recent years. These are attributed to both political-economic factors, including economic growth, an improved employment outlook, and the successful removal of former raskols, or criminal gangs, by business-oriented settlers, and also to institutional factors, such as the failure of criminal gangs to become institutionalized and the ability of local leadership to prevent the escalation of ethnic conflict and youth-related crime.This report examines the capabilities of mediation institutions in mixed settlements where the majority of the population of Papua New Guinea’s (PNG) largest cities live and work. This report focuses on mediation in mixed settlements, where the majority of the population of PNG’s cities live. Three dimensions of institutional capability are considered: i) efficiency (accessibility, affordability, timeliness, and sustainability), ii) power and authority, and iii) outcomes and legitimacy. Although the results are preliminary, as this initial investigation focused on, What is there and how it works, the research reveals significant differences in outcomes for different groups that need further clarification.